(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Objective: The objective of this academic work is to demonstrate evidences available in literature about the association among the pubertal maturation and health risk behavior in adolescents. Methods: It was used the database from MEDLINE/Pubmed, Scopus, Lilacs and Web of Science. The terms used in the research, with its variations, were “puberty”, “maturation”, “maturity”, “risk behaviors”, “risk factors”, “adolescent” and “student”. Results: Out of 838 manuscripts found in the databases, after the sorting and applied the eligibility criteria, remained in this systematic review 13 articles. Early maturation was associated significantly with the use of alcohol, cigarettes and illegal drugs, early sexual initiation, sedentary behaviors and involvement in fights, where girls showed higher prevalence. Conclusions: Henceforth, the results from the current study indicates that the early maturation is associated with health risk behaviors in adolescents, especially with the use of alcohol and cigarettes.